The Influence Of Discounts, Content Marketing And Influencer Marketing On Decisions To Purchase Scarlett Whitening Products At Tiktok Shop - Anggraeni, Melly Sri; Handayani, Langgeng Sri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Currently, promotion or marketing systems can be done using an online system, which has become a normal thing for entrepreneurs, whether a company or individual. Online promotion or marketing aims to provide information to potential buyers and for other purposes to increase interest from potential buyers in the products or services that have been offered. The aim of this research is to explain the influence of discounts, content marketing and influencer marketing in influencing purchasing decisions for Scarlett Whitening products. This research took a sample of 100 respondents who were students of the Bachelor of Management study program class of 2020 at Pelita Bangsa University who had purchased Scarlett Whitening products. Collecting data includes distributing questionnaires and literature study. The type of research used is quantitative. The analytical methods used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that discounts partially have a positive and significant effect on purchasing decisions, content marketing partially has a positive and significant effect on purchasing decisions and influencer marketing partially has a positive and significant effect on purchasing decisions. It can be concluded that 68.6% of purchasing decisions are influenced by discount variables, content marketing and influencer marketing while the remaining 31.4% of purchasing decisions are influenced by other variables not examined in this research